Factors Influencing Motivation for Exclusive Breastfeeding in Infants Aged 6-12 Months In the Work Area of ​​Karang Intan 2 Community Health Center - Anisa Fitri; Ika Friscila; Putri Yuliantie; Siti Noor Hasanah (Gayaku Publisher, 2026)
Background: Exclusive breastfeeding for the first six months of life is essential to improve maternal and child health. However, the coverage of exclusive breastfeeding has not fully reached the national target. Maternal motivation plays an important role in the success of exclusive breastfeeding and may be influenced by knowledge, family support, and the role of midwives. Objective: This study aimed to determine the level of maternal motivation and to analyze the relationship between knowledge, family support, and the role of midwives with maternal motivation in exclusive breastfeeding among mothers with infants aged 6–12 months at Karang Intan 2 Public Health Center. Methods: This study used a quantitative method with a cross-sectional design. The population consisted of 40 mothers with infants aged 6–12 months, and all were included as samples using total sampling. Data were collected using structured questionnaires and analyzed using univariate and bivariate analysis with Kendall’s Tau test at a significance level of 0.05. Results: Most respondents had high motivation (40%). Good knowledge (37.5%), high family support (37.5%), and good midwife role (40%) were observed. There were significant relationships between knowledge (p<0.05; τ=0.61), family support (p<0.05; τ=0.68), and the role of midwives (p<0.05; τ=0.72) with maternal motivation in exclusive breastfeeding. Conclusion: Knowledge, family support, and the role of midwives are significantly associated with maternal motivation in exclusive breastfeeding, with the role of midwives showing the strongest correlation.